Epidemiological analysis and assessment of the demand for pharmacotherapeutic monitoring of patients with thyroid cancer undergoing thyroidectomy (Research, Society and Development, 2023)
Thyroid cancer is the most common endocrine neoplasm in the world, with studies that have shown overdiagnosis and a real increase in advanced stages, where treatment can bring some complications to the patient. The aim of the study was to describe the epidemiological profile and assess, based on complications such as hypocalcemia, the need for pharmacotherapeutic follow-up. A retrospective observational study was carried out that evaluated the medical records, prescriptions and laboratory tests of 35 patients who underwent thyroidectomy for neoplasms in the first half of 2020. There was a prevalence of the diagnosis in females of 88.6%. The average age was 49.8 years; 60% of patients had comorbidities; the most prevalent histopathological diagnosis of thyroid cancer was papillary carcinoma with 62.1%; and, after the surgical approach, serum calcium was measured in the first 24 hours, with a rate of 48.5% of patients without an electronic medical record requesting exams. Most patients were discharged with a prescription of calcium (94%) and calcitriol (68%) for replacement, and 68.5% had outpatient medical follow-up. It is essential to evaluate the correct dosages of calcium and calcitriol due to hypokalemia, and a suggestion to the service is pharmacotherapeutic follow-up by the pharmacist to assess adherence to treatment and guidance on the correct use of medications.